La dactilopintura como técnica para el proceso de preescritura en niños de 5 a 6 años de la Escuela de Educación Básica “Capullitos”, ciudad de Riobamba. - Pineda Leon, Leslye Fernanda (2024)
The present investigative work titled; "Fingerprinting as a technique for the prewriting process in children aged 5 to 6 years at the Capullitos Basic Education School, city of Riobamba" had as its main objective to increase the good use of the grapho-plastic technique such as fingerprinting, for the improvement and acquisition of skills in the prewriting process. The methodology used in this project was qualitative, quantitative, non-experimental, bibliographic, descriptive, and explanatory; it was also configured as a field study, allowing all data to be obtained directly from the school. To collect information, an observation sheet was applied to 18 students, ten boys and eight girls, in which several activities were carried out and they were evaluated through observation. Then, the analysis, interpretation, and tabulation of the results were carried out, and it was evident that most children enjoyed and showed interest and enthusiasm when working with this technique. However, it was also possible to verify that some students have certain drawbacks. However, it was determined that this technique is applicable to children and that teachers are willing to implement it in their class hours, recognizing the great benefits of this technique and allowing children to have excellent development in their fine motor skills and, therefore, both a good result in the prewriting process. This research project is expected to contribute significantly to children's learning while strengthening their motor skills and improving their prewriting process through the fingerprinting technique